Key role of hydrochar in heterogeneous photocatalytic degradation of sulfamethoxazole using Ag3PO4-based photocatalysts. Issue 61 (4th November 2019) - Zhou, Li; Cai, Min; Zhang, Xu; Cui, Naxin; Chen, Guifa; Zou, Guo-yan
Abstract : To overcome the practical application limitations of Ag3 PO4 such as photocorrosion and relatively low efficiency of photogenerated carrier seperation, Ag3 PO4 particles were loaded onto hydrochar. Abstract : To overcome the practical application limitations of Ag3 PO4 such as photocorrosion and relatively low efficiency of photogenerated carrier seperation, Ag3 PO4 particles were loaded onto hydrochar. The particles in the composite had a smaller crystallite size and different phase structure with more edges than pure Ag3 PO4 particles. The as-prepared composite catalyst exhibited a different photocatalytic performance for sulfamethoxazole (SMX) degradation when varying the mass ratio of hydrochar and Ag3 PO4 . In addition to higher SMX degradation efficiency, the composite exhibited much higher TOC degradation efficiency, recycling stability, and less-toxic intermediate production. The composites enhanced visible light response, and accelerated electron transfer and photogenerated carrier separation as well. The addition of H2 O2 to the photocatalytic system enhanced the photocatalytic activity of the composite catalyst. According to a mechanistic examination, the hole (h + ) is the dominant reactive species for SMX degradation. This study provides new insight into high-efficiency, low cost, and easily prepared photocatalysts for pollution removal from water.